On the non-exclusivity of loan contracts: An empirical investigation - Hans Degryse; Vasso Ioannidou; Erik von Schedvin (Sveriges Riksbank, 2012)
A string of theoretical papers shows that the non-exclusivity of credit contracts generates important negative contractual externalities. Employing a unique dataset, we identify how these externalities affect the supply of credit. Using internal information on a creditor's willingness to lend, we find that a creditor reduces its credit supply when a borrower obtains a loan at another creditor (an outside loan). Consistent with the theoretical literature, the effect is more pronounced the larger the outside loans and it is muted if the initial creditor's existing and future loans retain seniority over the outside loans and are secured with valuable collateral.
Keywords: G21; G34; L13; L14; 330; non-exclusivity; contractual externalities; credit supply; debt seniority; Kreditwürdigkeit; Kreditrisiko; Kreditgeschäft; Adverse Selektion; Schweden